SPE Annual Technical Conference and Exhibition 2001
DOI: 10.2118/71322-ms
|View full text |Cite
|
Sign up to set email alerts
|

Halfdan: Developing Non-Structurally Trapped Oil in North Sea Chalk

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractMaersk Olie og Gas AS has as operator for the Danish Underground Consortium (DUC) discovered and initiated the development of the Halfdan accumulation located in the southern part of the Danish North Sea. The accumulation comprises oil and gas in a low permeability chalk reservoir located outside structural closure. This paper describes how the phased, fast track development of Halfdan was planned and executed while testing a new concept for constructing an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Brasher and Vagle, 1996;D'Heur, 1984) and the chalk reservoirs of the Danish Sector (e.g. Albrechtsen et al, 2001). Alternatively vertical migration through the chalk could be largely through fractures, and is regarded as a crucial factor by many (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brasher and Vagle, 1996;D'Heur, 1984) and the chalk reservoirs of the Danish Sector (e.g. Albrechtsen et al, 2001). Alternatively vertical migration through the chalk could be largely through fractures, and is regarded as a crucial factor by many (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocarbons migrating through the chalk have also been trapped non-structurally by intra-chalk seals. Accumulations of this kind (such as the Halfdan Field- Albrechtsen et al, 2001;Megson and Tygesen, 2005) have recently been found and there is potential for others to exist. Such accumulations may be more common in a situation where the permeability structure of the chalk is lower than previously envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…The Halfdan oil field (Jacobsen et al, 1999;Albrechtsen et al, 2001) is a chalk field with a permeability of 0.2-2 mD Water injection commenced in January 2001 from one injector, HDA-04. Injection seawater is supplied from the Dan FF platform via a 9 km long sub-sea pipeline.…”
Section: The Halfdan Fieldmentioning
confidence: 99%
“…The Halfdan field is laterally extensive and comprises a high porosity (25-30%), low permeability (0.5-2 mD) chalk reservoir located outside structural closure (Albrechtsen et al, 2001). The producing horizon is the Maastrichtian Age Chalk with a reservoir temperature and pressure of typically 80 • C and 4,200 psi, respectively.…”
Section: Case Study: the Halfdan Oilfieldmentioning
confidence: 99%